Research оn healthcare oxygen measures during the COVID-19 pandemic: latest trends and current priorities - O. P. Baula; O. O. Saliy; A. G. Halstian; T. V. Pazerska (The State Expert Center of the Ministry of Health of Ukraine, 2022)
Medical oxygen is a critically needed medicine in the treatment of coronavirus disease. During out breaks of the COVID-19 pandemic, the needs of health care institutions for medical oxygen increase by 5-6 times. The issue of the reliable functioning of the oxygen supply system of health care institutions during the COVID-19 pandemic is extremely urgent and requires systematic research. The purpose of the work was to conduct research on measures to provide oxygen to health care facilities during the COVID-19 pandemic, to establish risk factors in its production and supply, and to determine priority directions for guaranteeing the ability to provide medical assistance in the treatment of coronavirus disease. The methods of systematic approach, bibliographic, information search, marketing analysis, as well as generalization and analysis were used during the research. The study showed that medical use of oxygen as a medicine, oxygen produced by medical devices, and technical oxygen was allowed at the state level. Domestic manufacturers produce medical oxygen that meets all regulatory requirements for medicinal products. In Ukraine, 36 drugs based on medical oxygen are registered, the production of which is carried out by 26 enterprises that have licenses for the production of medicinal products. During the pandemic, it was allowed for medical use of technical oxygen, which should meet the quality indicators of medical oxygen. The use of oxygen, which is produced by medical devices, which include oxygen generators and oxygen concentrators, which must meet the requirements of the Technical Regulations, became a significant measure for the expansion of oxygen therapy. During the implementation of all measures to provide oxygen, there are risks of a national and branch nature, as well as specific risks associated with the characteristics of different types of oxygen (oxygen as a medicine, oxygen produced by medical devices, technical oxygen). The identified list of risks and their analysis in the provision of oxygen to health care facilities during the COVID-19 pandemic will provide an opportunity to develop the concept of general risk assessment and risk management processes to guarantee the ability to provide adequate medical care in the treatment of coronavirus disease